2004
DOI: 10.7861/clinmedicine.4-5-424
|View full text |Cite
|
Sign up to set email alerts
|

Influence of guidelines on CPR decisions: an audit of clerking proforma

Abstract: , as new guidelines and a proforma were introduced. For the first audit, data were collected from 75 departmental discharges. Following introduction of a proforma, six point prevalence audits were performed of all elderly care inpatients. Consultant documentation improved from 27/75 (36%) to 102/109 (94%), 135/148 (91%), 133/140 (95%), 96/119 (81%), 148/157 (94%) and 167/169 (98%) in audits 2, 3, 4, 5, 6 and 7 respectively. The percentages of decisions that were Do Not Attempt Resuscitation (DNAR) were 64% 72%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…3 There is evidence that obligatory discussions with patients before making every CPR decision results in a significant fall in the number of decisions relating to CPR. 4 In our study only 53% of patients who had seen the document chose to read it, indicating that a considerable proportion declined information on CPR when given the opportunity. Of those who did read the summary document only a quarter requested the detailed CPR information leaflet and they did not discuss it any further.…”
Section: Discussionmentioning
confidence: 89%
“…3 There is evidence that obligatory discussions with patients before making every CPR decision results in a significant fall in the number of decisions relating to CPR. 4 In our study only 53% of patients who had seen the document chose to read it, indicating that a considerable proportion declined information on CPR when given the opportunity. Of those who did read the summary document only a quarter requested the detailed CPR information leaflet and they did not discuss it any further.…”
Section: Discussionmentioning
confidence: 89%
“…Diggory's team 37 continued the audit cycles from their 2003 study and found that removing the statement indicating that all DNACPR decisions should be discussed with the patient increased the recording of resuscitation status and the number of DNACPR decisions issued. Piers et al 38 updated the DNACPR form to emphasise the reason for the DNACPR decision and involvement of others (surrogates, nurses) in the decision-making process.…”
Section: Do-not-attempt-cardiopulmonary-resuscitation Documentationmentioning
confidence: 99%
“…Over half (20/37) of the studies were conducted in the USA, 22,25,[28][29][30][31]39,41,42,45,[47][48][49][50][52][53][54][55][56][57] nine were conducted in the UK, 26,[32][33][34][35]37,40,43,44 two were conducted in Australia 23,24 and one study was conducted in each of Germany, 46 Belgium, 38 Switzerland, 51 the Netherlands, 16 Singapore 36 and Saudi Arabia. 27 …”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations